Laboratorium Patologi, Entomologi dan Mikrobiologi Fak. Pertanian dan Peternakan UIN Suska Riau. - Mokhamad Irfan (Kutubkhanah, 2013)
The Development of bioethanol from agricultural waste is not expected to be a problem in the competition between non-fossil fuel development with human consumption and animal feed. On the other hand, it can improve the quality of the environment for the better. This study aims to develop a bio-ethanol as an alternative energy source and to optimize the utilization of agricultural waste to produce bioethanol. Agricultural wastes are used: palm midrib, sweet corn stalks wastes, bagasse, sago pulp, sawdust, and tankos palm. Optimization of bioethanol production begins of fermentation time on a scale of 1 L and the concentration of substrate for palm midrib waste, waste of sweet corn stalks, bagasse and sago pulp. Volume stater given as much as 10% of the composition of the medium. For sawdust substrate and tankos, bioethanol production process is done a scale of 20 L. The fastest time for substrate fermentation of bagasse, sweet corn stalks and midrib of palm oil obtained within 72 hours with ethanol levels produced respectively 3.1%, 0.97%, 1.0%, while the dregs of sago for 120 hours at 1%. Increasing the concentration of the substrate at the optimum fermentation time can not increase the levels of ethanol produced. The best time to produce bioethanol fermentation of tankos is for 6 days with levels of 2.5%, while sawdust bioethanol terhasil not as contaminated by other microbes. Increasing the scale of production of 1 L to 20 L had lower levels of ethanol were produced in all the waste substrate used. The need for improved methods of production processes and methods of measurement due to differences in raw materials and substrates will provide physical and chemical differences in the character of the fermentation process.